2020
DOI: 10.1155/2020/8865958
|View full text |Cite
|
Sign up to set email alerts
|

Energy Dissipation-Based Method for Strength Determination of Rock under Uniaxial Compression

Abstract: The energy conversion in rocks has an important significance for evaluation of the stability and safety of rock engineering. In this paper, some uniaxial compression tests for fifteen different rocks were performed. The evolution characteristics of the total energy, elastic energy, and dissipated energy for the fifteen rocks were studied. The dissipation energy coefficient was introduced to study the evolution characteristics of rock. The evolution of the dissipation energy coefficient for different rocks was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
(38 reference statements)
0
12
0
Order By: Relevance
“…Under dynamic loads, rock damage or fracture may occur and energy consumption happens [5][6][7]. Accordingly, it is of importance to investigate energy dissipation in the process of rock fracture [8][9][10][11][12][13][14][15]. Under static loads, experimental studies have confirmed that the deformation and failure of rock is a process of energy input, dissipation, and release.…”
Section: Introductionmentioning
confidence: 99%
“…Under dynamic loads, rock damage or fracture may occur and energy consumption happens [5][6][7]. Accordingly, it is of importance to investigate energy dissipation in the process of rock fracture [8][9][10][11][12][13][14][15]. Under static loads, experimental studies have confirmed that the deformation and failure of rock is a process of energy input, dissipation, and release.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that when external load is applied on rock sample no heat is lost [33,34], according to the first law of thermodynamics the total energy is derived using Equation (1).…”
Section: Rock Failure Modesmentioning
confidence: 99%
“…e results are closer to the nature of rock damage by exploring the damage evolution during rock loading from the perspective of energy dissipation. He et al [14] introduced the dissipated energy coefficient to study the energy evolution characteristics of rocks and proposed a method to determine the rock burst proneness and crack propagation in rocks. Liu et al [15] established a damage constitutive model of rocks from the perspective of dissipated energy to describe the behavior of rocks under cyclic loading.…”
Section: Introductionmentioning
confidence: 99%